Experiences of social services received by families with children with disabilities outside Lithuania - Raimonda Rimkutė; Aristida Čepienė (Taikomieji Moksliniai Tyrimai)
Social services aim to provide assistance to a person or family who, due to various problems, partially or completely do not have the abilities or opportunities to take care of themselves and participate in public life. People with various disabilities, especially children, can take care of themselves the least. Therefore, the provision of social services to children with disabilities is one of the welfare state's criteria in the field of social policy. Since the well-being of children with disabilities is inseparable from that of adults, i.e. i.e. the well-being of the families raising them, therefore the provision of social support must be aimed at ensuring the well-being of the whole family. The purpose of this article is to analyze the experience of social services received by families raising children with disabilities in Norway. 6 mothers living in Norway raising children with disabilities participated in the study. Qualitative content analysis revealed that in Norway, families raising children with disabilities are given the opportunity to receive two types of services - monetary benefits and social services. The attitude towards the social services provided in Norway is favorable, families are satisfied with the availability and comprehensiveness of social services, as well as social justice, appropriateness and comprehensiveness. However, families are faced with the availability of some social services, depending on the geographical location, the lack of service providers and their competence to work with children with different disabilities.